Altered spontaneous cortical activity predicts pain perception in individuals with cerebral palsy. Issue 2 (4th April 2022) - Trevarrow, Michael P.; Reelfs, Anna; Ott, Lauren R.; Penhale, Samantha H.; Lew, Brandon J.; Goeller, Jessica; Wilson, Tony W.; Kurz, Max J.
Abstract: Cerebral palsy is the most common paediatric neurological disorder and results in extensive impairment to the sensorimotor system. However, these individuals also experience increased pain perception, resulting in decreased quality of life. In the present study, we utilized magnetoencephalographic brain imaging to examine whether alterations in spontaneous neural activity predict the level of pain experienced in a cohort of 38 individuals with spastic diplegic cerebral palsy and 67 neurotypical controls. Participants completed 5 min of an eyes closed resting-state paradigm while undergoing a magnetoencephalography recording. The magnetoencephalographic data were then source imaged, and the power within the delta (2–4 Hz), theta (5–7 Hz), alpha (8–12 Hz), beta (15–29 Hz), low gamma (30–59 Hz) and high gamma (60–90 Hz) frequency bands were computed. The resulting power spectral density maps were analysed vertex-wise to identify differences in spontaneous activity between groups. Our findings indicated that spontaneous cortical activity was altered in the participants with cerebral palsy in the delta, alpha, beta, low gamma and high gamma bands across the occipital, frontal and secondary somatosensory cortical areas (all p FWE < 0.05). Furthermore, we also found that the altered beta band spontaneous activity in the secondary somatosensory cortices predicted heightened pain perception in the individuals with cerebral palsy ( P = 0.039). Overall, these results demonstrate that spontaneous cortical activity within individuals with cerebral palsy is altered in comparison to their neurotypical peers and may predict increased pain perception in this patient population. Potentially, changes in spontaneous resting-state activity may be utilized to measure the effectiveness of current treatment approaches that are directed at reducing the pain experienced by individuals with cerebral palsy. Abstract : Trevarrow et al . report alterations in spontaneous cortical activity across multiple spectral ranges in individuals with cerebral palsy. Interestingly, altered spontaneous activity in the beta range was correlated with increased pain perception in the secondary somatosensory cortices. These findings provide a new understanding of the neurological correlates of pain in cerebral palsy. Graphical Abstract: Graphical Abstract